Problemy ekonomiczne rewolucji naukowo-technicznej na współczesnym etapie rozwoju gospodarki socjalistycznej - Striełkowskij, J. K. (Wydział Prawa i Administracji UAM, 1973)
The influence of techno-scientific revolution on the rate of growth of the socialist countries can and ought to be extended through the all-round introduction of new techniques into production. In the past the science and production were completely or almost completely seperated with each other. The links between science and production were developing so slowly that it's a long time since the new scientific idea was introduced into production. Such a situation was due to the fact that science has been regarded as the process of satisfying the human curiosity with no reference to the actual problems of society. Arising of the close links and other interrelations between science, technology and economy has been the most visible feature of the techno-scientific revolution. At the presence further development of science and technics is characterized by regular advancing the introduction of technical progress and scientific inventions into production. The modernization of national economy on the basis of the most advanced technology and integration of the achievments of techno-scientific revolution with the social transformations constitutes the principal directions of the economic strategy of USSR in the new five-year plan.
Economic Problems of Techno-Scientific Revolution at the Present Stage of Development of the Socialist Economy